Evolution of strategic risks under future scenarios for improved utility master plans. (1st January 2016) - Luís, Ana; Lickorish, Fiona; Pollard, Simon
Abstract: Integrated, long-term risk management in the water sector is poorly developed. Whilst scenario planning has been applied to singular issues (e.g. climate change), it often misses a link to risk management because the likelihood of impacts in the long-term are frequently unaccounted for in these analyses. Here we apply the morphological approach to scenario development for a case study utility, Empresa Portuguesa das Águas Livres (EPAL). A baseline portfolio of strategic risks threatening the achievement of EPAL's corporate objectives was evolved through the lens of three future scenarios, 'water scarcity', 'financial resource scarcity' and 'strong economic growth', built on drivers such as climate, demographic, economic, regulatory and technological changes and validated through a set of expert workshops. The results represent how the baseline set of risks might develop over a 30 year period, allowing threats and opportunities to be identified and enabling strategies for master plans to be devised. We believe this to be the first combined use of risk and futures methods applied to a portfolio of strategic risks in the water utility sector. Graphical abstract: Highlights: First combined application of risk and futures analysis in the water utility sector. Three future scenarios developed 'in-house' using the morphological approach. Long-term evolution of interrelated financial, operational and reputational risks. A novel holistic approach to support water utility master planning. Developed and tested in the context of a large water supply utility.